People and organizational management in construction - Naoum, S. G. (Thomas Telford, 2001)
This text offers an extended dictionary of key management concepts for professionals and students alike in the industry. It helps the reader, through an applied approach to management, to search for the most appropriate ways of improving their organization's performance and effectiveness.